A high temperature piezoelectric ceramic and a preparation method thereof
By introducing lanthanide doping and reasonable preparation technology into piezoelectric ceramics, the existing piezoelectric ceramics are solved by restricting application and environmental hazards in high-temperature environments, and high-temperature pressure with high temperature stability and environmental protection are achieved Electric ceramic material.
Patent Information
- Application Number
- CN202411780395.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-05
AI Technical Summary
Existing piezoelectric ceramics are limited in applications in high temperature environments, and their manufacturing, use and waste disposal pose a threat to human health and the environment.
Using lanthanide-doped high-temperature piezoelectric ceramic materials, the ceramic sintering activity and piezoelectric properties are improved through reasonable crystal structure and dopant ratio, and appropriate pre-firing and sintering conditions are used during the preparation process to ensure that High temperature stability and environmental protection of ceramics.
The high Curie temperature and good piezoelectric properties of high-temperature piezoelectric ceramics are achieved, meeting the needs of the high-temperature piezoelectric field, while avoiding the use of lead and reducing the harm to the environment and health.
Smart Images

Figure CN119219416B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of piezoelectric ceramic materials, in particular to a high-temperature piezoelectric ceramic and a preparation method thereof. Background Art
[0002] According to the differences in physical and chemical properties of different materials, materials can be divided into organic, inorganic and composite materials. According to the use of materials, materials can be divided into electronic, architectural, biological, energy materials, etc. Electronic materials are mainly used in electronic technology and microelectronic technology, mainly including dielectric, semiconductor, ferroelectric, piezoelectric, metal, magnetic, optoelectronic, and electromagnetic wave shielding materials.
[0003] Piezoelectric ceramics are a type of electronic material with piezoelectric properties, mainly composed of ferroelectric grains. The spontaneous polarization orientation of the grains in the ceramic is random, and there is no spontaneous polarization in the ceramic macroscopically, that is, the ceramic has no piezoelectricity. When the ceramic end surface is coated with electrodes and placed under a DC electric field for polarization treatment, the disordered spontaneous polarization vector in the ceramic will be preferentially oriented along the direction of the external electric field, and a certain macroscopic residual polarization intensity will still be retained inside the ceramic after the electric field disappears. At this time, the ceramic has certain piezoelectric properties.
[0004] Lead zirconate titanate (PZT)-based ceramics are the main system of commercial piezoelectric ceramics, but the manufacturing, use and waste disposal of this type of ceramics will cause great harm to human health and the living environment. At present, the application temperature of PZT ceramics is limited (<180°C), and it is difficult to use in high temperature environments. Therefore, the research of environmentally friendly high-temperature lead-free piezoelectric ceramics is imperative. Summary of the invention
[0005] Purpose of the invention: In view of the above technical problems, the present invention proposes a high-temperature piezoelectric ceramic and a preparation method thereof.
[0006] The technical solutions adopted are as follows:
[0007] A high temperature piezoelectric ceramic, the structural formula of which is shown below:
[0008] (1-xy)(Bi 1-p Ln p )FeO3-xBa(Ti 1-q Al q )O3-yBiYbO3-zwt%GeO2
[0009] Among them, Ln is a lanthanide element;
[0010] 0.1≤x≤0.5, 0.01≤y≤0.05;
[0011] 0.1≤z≤1;
[0012] 0.1≤p≤0.5, 0.01≤q≤0.05.
[0013] Furthermore, Ln is any one or more combinations of Nd, Dy, Tb, and Gd.
[0014] Furthermore, 0.15≤x≤0.3, 0.02≤y≤0.04.
[0015] Further, x=0.25, y=0.03.
[0016] Further, 0.2≤z≤0.5.
[0017] Further, z=0.4.
[0018] Further, 0.15≤p≤0.3, 0.03≤q≤0.04.
[0019] Further, p=0.2, q=0.04.
[0020] The present invention also provides a method for preparing a high-temperature piezoelectric ceramic:
[0021] Mix Bi2O3, Ln2O3 and Fe2O3, ball-mill them, dry them and pre-fire them at 750-850°C to obtain the first material; mix BaCO3, TiO2 and Al2O3, ball-mill them, dry them and pre-fire them at 800-900°C to obtain the second material; mix the first material, the second material, BiYbO3 and GeO2, ball-mill them again, dry them, granulate them, press them, debind them and sinter them.
[0022] Furthermore, the sintering temperature is 1000-1050° C., and the sintering time is 1-4 hours.
[0023] Beneficial effects of the present invention:
[0024] The present invention provides a high-temperature piezoelectric ceramic. Lanthanide elements are often introduced into PZT ceramics as donors or soft dopants, thereby significantly improving their ferroelectric and piezoelectric properties. The similarity between BF-BT-based piezoelectric ceramics and PZT piezoelectric ceramics in crystal structure and MPB behavior indicates that the piezoelectric properties of BF-BT-based ceramics can be optimized using a similar method in PZT ceramics. Lanthanide element doping improves the sintering activity of piezoelectric ceramics, and enables the piezoelectric ceramics to maintain good piezoelectric properties and a high Curie temperature, fully meeting the needs of the high-temperature piezoelectric field.
[0025] A1 3+ The solid solubility in piezoelectric ceramics is limited. After doping, it will gather at the grain boundary, causing lattice distortion, promoting material diffusion and grain growth. 3+ Replace Ti 4+Oxygen vacancies will appear, and oxygen vacancies have a pinning effect on the grain boundary movement of ceramics, which is also beneficial to improve the structural density and piezoelectric properties;
[0026] Bismuth-based perovskite oxide BiYbO3 has a high Curie temperature and good piezoelectric properties, and can be well dissolved in BF-BT-based piezoelectric ceramics. 3+ A liquid phase can also be formed during the sintering process, promoting mass transfer and structural densification;
[0027] The high-temperature piezoelectric ceramics prepared by the present invention have a high Curie temperature and good piezoelectric performance, and do not contain lead elements, and will not cause harm to human health and the living environment during the manufacturing, use and waste treatment processes. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a SEM image of the high-temperature piezoelectric ceramic prepared in Example 1 after polishing and thermal corrosion treatment. It can be seen that its internal structure is relatively dense without obvious pores. DETAILED DESCRIPTION
[0029] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.
[0030] Embodiment 1:
[0031] This embodiment provides a high temperature piezoelectric ceramic, the structural formula of which is as follows:
[0032] 0.72(Bi 0.8 Tb 0.2 )FeO3-0.25Ba(Ti 0.96 Al 0.04 )O3-0.03BiYbO3-0.4wt%Ge
[0033] The preparation method of the above-mentioned high temperature piezoelectric ceramic is as follows:
[0034] Bi2O3, Tb2O3 and Fe2O3 were added to a ball mill, and anhydrous ethanol was used as the ball milling medium. After ball milling for 10 hours on a planetary ball mill, the ball mill was dried, placed in a mold and pressed into tablets at 10 MPa, and then heated to 800°C at a rate of 5°C / min for pre-calcination for 2 hours. After the pre-calcination, the product was crushed to obtain the first material. BaCO3, TiO2 and Al2O3 were added to a ball mill, and anhydrous ethanol was used as the ball milling medium. After ball milling for 10 hours on a planetary ball mill, the ball mill was dried, placed in a mold and pressed into tablets at 10 MPa, and then heated to 800°C at a rate of 5°C / min for pre-calcination for 2 hours. The mixture is heated to 850°C at a rate of 100°C and pre-fired for 2 hours. After the pre-fired, the product is crushed to obtain the second material. The first material, the second material, BiYbO3 and GeO2 are added into a ball mill, and anhydrous ethanol is used as the ball milling medium. The mixture is ball milled again for 10 hours on a planetary ball mill and dried. A 10wt% concentration of PVA solution is added as a binder to form granules. The granules are passed through a 120-mesh sieve and placed in a mold and pressed into a billet at a pressure of 100 MPa. The billet is heated to 650°C at a rate of 1°C / min and kept for debinding for 1 hour. The temperature is then raised to 1050°C and kept for sintering for 2 hours.
[0035] Embodiment 2:
[0036] This embodiment provides a high temperature piezoelectric ceramic, the structural formula of which is as follows:
[0037] 0.72(Bi 0.8 Nd 0.2 )FeO3-0.25Ba(Ti 0.96 Al 0.04 )O3-0.03BiYbO3-0.4wt%Ge
[0038] The preparation method of the above-mentioned high temperature piezoelectric ceramic is as follows:
[0039] Bi2O3, Nd2O3 and Fe2O3 were added to a ball mill, and anhydrous ethanol was used as the ball milling medium. After ball milling for 10 hours on a planetary ball mill, the mixture was dried and placed in a mold and pressed into tablets at 10 MPa. The mixture was heated to 800°C at a rate of 5°C / min and pre-calcined for 2 hours. After the pre-calcination, the product was crushed to obtain the first material. BaCO3, TiO2 and Al2O3 were added to a ball mill, and anhydrous ethanol was used as the ball milling medium. After ball milling for 10 hours on a planetary ball mill, the mixture was dried and placed in a mold and pressed into tablets at 10 MPa. The mixture was heated to 800°C at a rate of 5°C / min and pre-calcined for 2 hours. After the pre-calcination, the product was crushed to obtain the first material. The mixture is heated to 850°C at a rate of 100°C and pre-fired for 2 hours. After the pre-fired, the product is crushed to obtain the second material. The first material, the second material, BiYbO3 and GeO2 are added into a ball mill, and anhydrous ethanol is used as the ball milling medium. The mixture is ball milled again for 10 hours on a planetary ball mill and dried. A 10wt% concentration of PVA solution is added as a binder to form granules. The granules are passed through a 120-mesh sieve and placed in a mold and pressed into a billet at a pressure of 100 MPa. The billet is heated to 650°C at a rate of 1°C / min and kept for debinding for 1 hour. The temperature is then raised to 1050°C and kept for sintering for 2 hours.
[0040] Embodiment 3:
[0041] This embodiment provides a high temperature piezoelectric ceramic, the structural formula of which is as follows:
[0042] 0.72(Bi 0.8 Dy 0.2 )FeO3-0.25Ba(Ti 0.96 Al 0.04 )O3-0.03BiYbO3-0.4wt%GeO2
[0043] The preparation method of the above-mentioned high temperature piezoelectric ceramic is as follows:
[0044] Bi2O3, Dy2O3 and Fe2O3 were added to a ball mill, and anhydrous ethanol was used as the ball milling medium. After ball milling for 10 hours on a planetary ball mill, the mixture was dried and placed in a mold and pressed into tablets at 10 MPa. The mixture was then heated to 800°C at a rate of 5°C / min and pre-calcined for 2 hours. After the pre-calcination, the product was crushed to obtain the first material. BaCO3, TiO2 and Al2O3 were added to a ball mill, and anhydrous ethanol was used as the ball milling medium. After ball milling for 10 hours on a planetary ball mill, the mixture was dried and placed in a mold and pressed into tablets at 10 MPa. The mixture was then heated to 800°C at a rate of 5°C / min and pre-calcined for 2 hours. After the pre-calcination, the product was crushed to obtain the first material. The mixture is heated to 850°C at a rate of 100°C and pre-fired for 2 hours. After the pre-fired, the product is crushed to obtain the second material. The first material, the second material, BiYbO3 and GeO2 are added into a ball mill, and anhydrous ethanol is used as the ball milling medium. The mixture is ball milled again for 10 hours on a planetary ball mill and dried. A 10wt% concentration of PVA solution is added as a binder to form granules. The granules are passed through a 120-mesh sieve and placed in a mold and pressed into a billet at a pressure of 100 MPa. The billet is heated to 650°C at a rate of 1°C / min and kept for debinding for 1 hour. The temperature is then raised to 1050°C and kept for sintering for 2 hours.
[0045] Embodiment 4:
[0046] This embodiment provides a high temperature piezoelectric ceramic, the structural formula of which is as follows:
[0047] 0.72(Bi 0.8 G 0.2 )FeO3-0.25Ba(Ti 0.96 Al 0.04 )O3-0.03BiYbO3-0.4wt%GeO2
[0048] The preparation method of the above-mentioned high temperature piezoelectric ceramic is as follows:
[0049] Bi2O3, Gd2O3 and Fe2O3 were added to a ball mill, and anhydrous ethanol was used as the ball milling medium. After ball milling for 10 hours on a planetary ball mill, they were dried, placed in a mold and pressed into tablets at 10 MPa, and then heated to 800°C at a rate of 5°C / min for pre-calcination for 2 hours. After the pre-calcination, the product was crushed to obtain the first material. BaCO3, TiO2 and Al2O3 were added to a ball mill, and anhydrous ethanol was used as the ball milling medium. After ball milling for 10 hours on a planetary ball mill, they were dried, placed in a mold and pressed into tablets at 10 MPa, and then heated to 800°C at a rate of 5°C / min for pre-calcination for 2 hours. The mixture is heated to 850°C at a rate of 100°C and pre-fired for 2 hours. After the pre-fired, the product is crushed to obtain the second material. The first material, the second material, BiYbO3 and GeO2 are added into a ball mill, and anhydrous ethanol is used as the ball milling medium. The mixture is ball milled again for 10 hours on a planetary ball mill and dried. A 10wt% concentration of PVA solution is added as a binder to form granules. The granules are passed through a 120-mesh sieve and placed in a mold and pressed into a billet at a pressure of 100 MPa. The billet is heated to 650°C at a rate of 1°C / min and kept for debinding for 1 hour. The temperature is then raised to 1050°C and kept for sintering for 2 hours.
[0050] Comparative Example 1:
[0051] The same as Example 1, except that BiFeO3 is used instead of (Bi 0.8 Tb 0.2 )FeO3;
[0052] This comparative example provides a high temperature piezoelectric ceramic, the structural formula of which is shown below:
[0053] 0.72BiFeO3-0.25Ba(Ti 0.96 Al 0.04 )O3-0.03BiYbO3-0.4wt%GeO2
[0054] The preparation method of the above-mentioned high temperature piezoelectric ceramic is as follows:
[0055] Bi2O3 and Fe2O3 are added to a ball mill, anhydrous ethanol is used as the ball milling medium, and the ball milling is performed on a planetary ball mill for 10 hours, then dried, placed in a mold and pressed into a sheet at 10MPa, and then heated to 800℃ at a speed of 5℃ / min for pre-calcination for 2 hours. After the pre-calcination, the product is crushed to obtain the first material, BaCO3, TiO2, and Al2O3 are added to a ball mill, anhydrous ethanol is used as the ball milling medium, and the ball milling is performed on a planetary ball mill for 10 hours, then dried, placed in a mold and pressed into a sheet at 10MPa, and then heated to 800℃ at a speed of 5℃ / min for pre-calcination for 2 hours. The temperature is raised to 850°C and pre-fired for 2 hours. After the pre-fired, the product is crushed to obtain the second material. The first material, the second material, BiYbO3, and GeO2 are added to a ball mill, and anhydrous ethanol is used as the ball milling medium. They are ball-milled again on a planetary ball mill for 10 hours and then dried. A 10wt% concentration of PVA solution is added as a binder to make granules. The obtained granules are passed through a 120-mesh sieve and placed in a mold and pressed into a billet under a pressure of 100 MPa. The billet is heated to 650°C at a rate of 1°C / min and kept for debinding for 1 hour. Then the temperature is continued to be raised to 1050°C and kept for sintering for 2 hours.
[0056] Comparative Example 2:
[0057] The same as Example 1, except that BaTiO3 is used instead of Ba(Ti 0.96 Al 0.04 )O3;
[0058] This comparative example provides a high temperature piezoelectric ceramic, the structural formula of which is shown below:
[0059] 0.72(Bi 0.8 Tb 0.2 )FeO3-0.25BaTiO3-0.03BiYbO3-0.4wt%GeO2
[0060] The preparation method of the above-mentioned high temperature piezoelectric ceramic is as follows:
[0061] Bi2O3, Tb2O3 and Fe2O3 were added to a ball mill, and anhydrous ethanol was used as the ball milling medium. After ball milling for 10 hours on a planetary ball mill, the mixture was dried and placed in a mold and pressed into tablets at 10 MPa. The mixture was then heated to 800°C at a rate of 5°C / min and pre-fired for 2 hours. After the pre-fired, the product was crushed to obtain the first material. BaCO3 and TiO2 were added to a ball mill, and anhydrous ethanol was used as the ball milling medium. After ball milling for 10 hours on a planetary ball mill, the mixture was dried and placed in a mold and pressed into tablets at 10 MPa. The mixture was then heated to 800°C at a rate of 5°C / min and pre-fired for 2 hours. After the pre-fired, the product was crushed to obtain the first material. The temperature is raised to 850°C and pre-fired for 2 hours. After the pre-fired, the product is crushed to obtain the second material. The first material, the second material, BiYbO3, and GeO2 are added to a ball mill, and anhydrous ethanol is used as the ball milling medium. They are ball-milled again on a planetary ball mill for 10 hours and then dried. A 10wt% concentration of PVA solution is added as a binder to make granules. The obtained granules are passed through a 120-mesh sieve and placed in a mold and pressed into a billet under a pressure of 100 MPa. The billet is heated to 650°C at a rate of 1°C / min and kept for debinding for 1 hour. Then the temperature is continued to be raised to 1050°C and kept for sintering for 2 hours.
[0062] Comparative Example 3:
[0063] It is basically the same as Example 1, except that BiYbO3 is not added.
[0064] Comparative Example 4:
[0065] Basically the same as Example 1, except that GeO2 is not added.
[0066] Performance Test:
[0067] The high-temperature piezoelectric ceramics prepared in Examples 1-4 of the present invention and Comparative Examples 1-4 were polished and silvered, and polarized in a 7 kV / mm electric field in silicone oil at 100°C for 15 minutes and then left for one day as test samples;
[0068] The high temperature dielectric temperature spectrum test system (GJW-I) was used to measure the change of the dielectric constant of the sample with temperature, and the Curie temperature Tc was determined. The ZJ-3A quasi-static d 33 The piezoelectric constant d of the test specimen is measured by the measuring instrument 33 The measurement frequency is 110 Hz, and the Agilent 4294A precision impedance analyzer is used to measure the electrical properties of the sample, such as the mechanical quality factor Qm, the planar electromechanical coupling coefficient kp, and the dielectric loss tanδ.
[0069] The test results are shown in Table 1 below:
[0070] ;
[0071] It can be seen from Table 1 above that the high-temperature piezoelectric ceramics prepared in the present invention have a higher Curie temperature and better piezoelectric properties.
[0072] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high temperature piezoelectric ceramic, characterized in that: Its structural formula is as follows: <h2 style=";text-align:left;direction:ltr">(1-xy)(Bi<h2 style=";text-align:left;direction:ltr"> 1-p <h2 style=";text-align:left;direction:ltr"> Ln<h2 style=";text-align:left;direction:ltr"> p <h2 style=";text-align:left;direction:ltr"> )FeO3-xBa(Ti<h2 style=";text-align:left;direction:ltr"> 1-q <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> q <h2 style=";text-align:left;direction:ltr"> )O3-yBiYbO3-zwt%GeO2 Among them, Ln is a lanthanide element; 0.1≤x≤0.5, 0.01≤y≤0.05; 0.1≤z≤1; 0.1≤p≤0.5, 0.01≤q≤0.
05.
2. The high temperature piezoelectric ceramic according to claim 1, characterized in that: Ln is any one or more combinations of Nd, Dy, Tb, and Gd.
3. The high temperature piezoelectric ceramic according to claim 1, characterized in that: 0.15≤x≤0.3, 0.02≤y≤0.
04.
4. The high temperature piezoelectric ceramic according to claim 1, characterized in that: x=0.25,y=0.
03.
5. The high temperature piezoelectric ceramic according to claim 1, characterized in that: 0.2≤z≤0.5。 6. The high temperature piezoelectric ceramic according to claim 1, characterized in that: z=0.4。 7. The high temperature piezoelectric ceramic according to claim 1, characterized in that: p=0.2,q=0.
04.
8. A method for preparing a high temperature piezoelectric ceramic according to any one of claims 1 to 7, characterized in that: Mix Bi2O3, Ln2O3 and Fe2O3, ball-mill them, dry them and pre-fire them at 750-850°C to obtain the first material; mix BaCO3, TiO2 and Al2O3, ball-mill them, dry them and pre-fire them at 800-900°C to obtain the second material; mix the first material, the second material, BiYbO3 and GeO2, ball-mill them again, dry them, granulate them, press them, debind them and sinter them.
9. The method for preparing a high temperature piezoelectric ceramic according to claim 8, characterized in that: The sintering temperature is 1000-1050°C, and the sintering time is 1-4h.
Citation Information
Patent Citations
Bismuth ferrite-barium titanate high-temperature lead-free piezoelectric ceramic material and preparation method thereof
CN116444260A
Low-loss high-curie-point bismuth ferrite-barium titanate lead-free piezoelectric ceramic material and preparation method thereof
CN118290137A